Formulasi dan Evaluasi Stabilitas Fisik Sediaan Krim Senyawa Astaxanthin - Robert Tungadi; Mahdalena Sy. Pakaya; priliya wati d.as'ali (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
This study aims to formulate and evaluate the preparation of an anti-aging cream made from astaxanthin. Astaxanthin has antioxidant activity, as well as other carotenoid compounds. Astaxanthin shows more significant antioxidant activity than ?-carotene; thus,developing astaxanthin compounds in cream preparations is necessary. This type of experimental laboratory research compares three different concentrations of astaxanthin compounds, including formula I (0.5%), formula II (0.75%), and formula III (1%). Evaluation of the astaxanthin compound cream preparations stability included organoleptic observations (smell, color, texture), pH test, homogeneity test, viscosity test, spreadability test, adhesion test, and freeze-thaw test. The results of the quality inspection of organoleptic preparations revealed no difference between the preparations in the form of color, smell, and texture.The homogeneity test showed a homogeneous preparation; the pH test produced was 5.5-5.8, the viscosity test of the preparation produced was 5140 Cp, 5250 Cp, and 7000 Cp, the adhesion test was 6.40-7.83 seconds, the dispersion test was 5-5.9 cm, and the Freeze-thaw test showed that there was no significant change in the pH test, organoleptic test, spreadability, adhesion, homogeneity, and viscosity. Thus, it can be concluded that the three astaxanthin compound cream formulas have good stability.